Temperature, Humidity, and Power Outage Monitoring System of Pamapersada Nusantara’s Server Racks - Eskandaru Erin Sadewa; Samuel Beta (JAICT, 2022)
Data center is a vital location that must be managed. The room contains central devices that are essential for operational continuity of the information system. Like the PT Pamapersada Nusantara data center, this room needs to be maintained according to standards. One thing that needs to be maintained is temperature, humidity, and electricity because they have a direct impact on IT equipment and can be potentially fatal if they are not in standard conditions. Meanwhile, the data center being researched uses manual checks for temperature, humidity, and electrical power supply. The problem is the inconsistency of the administrator in documenting these parameters and the lack of responsiveness of repairs if an anomaly occurs in the parameter value, because the data is not real time. This research aims to build a monitoring system for monitoring temperature, humidity, and power outage at the PT Pamapersada Nusantara data center which provides direct notifications to administrators. Current similar studies generally do not include the sensor location factor which is essential. The sensor installation is not randomly placed in the room, nor in the hot aisle or in the cold aisle, but in the server rack so that the temperature and humidity truly represent the surroundings of the device as ASHRAE recommend. Referring to ASHRAE, the standard temperature is 18° C - 27° C while the humidity is 20% - 60%. This research starts from a needs analysis through a survey, followed by equipment design, equipment testing by comparing with manual measuring tools. ESP8266 and DHT22 sensors are used, telegram as system output in the form of notifications. Notifications are sent when the temperature and humidity values are not in standard conditions, they are sent every day at 07.00 and 15.00, and they are sent if there is 5% increasing or decreasing values. The results show that the system successfully sends a notification on telegram when the conditions are met. Tests using comparisons with other measuring instruments also show a deviation of values below 2%. Measurements on the server rack show varying value depending on the occupancy of the rack and its position against the air conditioner